(untitled) (Archaeologia Adriatica, 2017)
The article deals with the archaeological material recorded over the past decade on the island of Silba and on its seabed. The island is located on the most important seafaring route that led from the northern to southern Adriatic. The source of the earliest – albeit scarce – information about its population is the island’s prehistoric hill-fort. As for the life on the island in Antiquity and Late Antiquity, the graves and sarcophagi recorded there can be used as evidence of it. In terms of the number of finds, the seabed off Silba is much richer than the island itself, particularly the area near Sveti Ante Cove and Cape Arat, where Antiquity remains and Modern Age glass objects were found. Grebeni – the neighboring group of three reefs – were also included in the excavations. They were fatal for numerous ships of the Antiquity, as well as for one Late Medieval ship and one Modern Age ship. The most important finds include those from a mid-1st-century AD ship (a large quantity of material which is mostly unique for the Adriatic), a bell from the second half of the 13th century, and a ship with mid-17th-century cannons, anchors and ceramics. We should add to these the find of a shipwreck with Baetical amphorae (type Dr. 20) – the first such find on the Adriatic seabed.